IMPLEMENTASI PASAL 25 PERATURAN DAERAH NOMOR 08 TAHUN 2014 TENTANG PENGELOLAAN SAMPAH DI KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Activities carried out by the people of Pekanbaru City will have an impact on the cleanliness of the environment, which is the beauty and comfort that is expected for people who live in the area. The result of this community activity is that more and more waste is generated from materials that are used up or materials that are no longer used, which come from household, industrial, and so on. The condition of waste facilities and infrastructure in Tampan District is still lacking because there are only TPS which are very few in number and are unable to accommodate all of the community's domestic waste.The Purpose of this research was to determine implementation of Local Regulation Number 8 of 2014 about recycling waste management in Pekanbaru, the factors that become the obstacle in adequate infrastructure and facilities in Pekanbaru and government’s effort to solve the problem of unavailability of waste management infrastructure and facilities in Pekanbaru.The type of this research used was Sociological Law research with field research techniques, interviews, and literature studies. This research was conducted in Pekanbaru. To obtain result of the research, the data obtained, both primary and secondary data are then analyzed using a qualitative approach which is further described. The results of this study concluded that the implementation of Local Regulation Number 08 of 2014 about recycling waste management in Pekanbaru through the implementation of waste management with a transport collection system, the Sustainable Development Goals Program (SDG), a program to increase the role of the community, the private sector and institutions basic education. The factors that become the obstacle in adequate infrastructure and facilities in Pekanbaru were the lack of a waste management budget, where financing in waste management carried out by the Department of Environment and Hygiene Pekanbaru were sourced from the APBD and user fees.Keywords: Implementation, Local Regulations, Management, Garbage